2022
DOI: 10.1021/jacs.2c08214
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Interlayer Shifting in Two-Dimensional Covalent Organic Frameworks Triggered by CO2 Sorption

Abstract: Two-dimensional covalent organic frameworks (2D COFs) have been widely viewed as rigid porous materials with smooth and reversible gas sorption isotherms. In the present study, we report an unusual hysteresis step in the CO2 adsorption isotherm of a 2D COF, TAPB-OMeTA. In situ powder X-ray diffraction (PXRD) measurements, computational modeling, and Pawley refinement indicate that TAPB-OMeTA experiences slight interlayer shifting during the CO2 adsorption process, resulting in a new structure that is similar b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…The field of covalent organic frameworks (COFs)porous structures consisting of organic building blocks reticulated via covalent bondshas gained significant attention in the last decade . COFs have emerged as robust materials for various applications, including gas storage and separation, energy storage, optoelectronics, and catalysis . COFs are perfect hosts for small-molecule catalysts due to their high crystallinity and porosity .…”
Section: Introductionmentioning
confidence: 99%
“…The field of covalent organic frameworks (COFs)porous structures consisting of organic building blocks reticulated via covalent bondshas gained significant attention in the last decade . COFs have emerged as robust materials for various applications, including gas storage and separation, energy storage, optoelectronics, and catalysis . COFs are perfect hosts for small-molecule catalysts due to their high crystallinity and porosity .…”
Section: Introductionmentioning
confidence: 99%
“…In recent few years, the dynamic nature of COFs, such as breathing effect and/or subnet sliding, has been observed by external stimuli (guest, light, pressure, etc. ). , With further development, more evidences show that most COFs are flexible to some extent due to the widespread noncovalent interactions in COF structures, such as π–π interactions, hydrogen bondings, Lewis acid–base interactions, etc. ,,, The strength of noncovalent interactions is relatively weak, and they are sensitive to external stimuli, which account for the dynamic nature in most COFs. For example, Zhao and co-workers reported that the weak π–π stacking interactions of 2D COFs can be destroyed by solvents, resulting in a reversible interlayer shift from AA-stacking structures in the dried state to quasi-AB-stacking structures in the solvated state, which clearly states the flexibility of COF structures .…”
Section: Introductionmentioning
confidence: 99%
“…Since Yaghi introduced the rst covalent organic framework (COF) in 2005, 12 the preparation of COFs has attracted signicant research interest. COFs have shown great potential for application in gas separation and storage, 13 adsorption of metal ions, 14 sensors, 15,16 optoelectronic devices, 17,18 and heterogeneous catalysis. 19,20 In particular, COFbased electrocatalysts have achieved considerable advances in the water cycle, [21][22][23] the carbon energy cycle, [24][25][26] and supercapacitors; 27,28 the developments of these energy storage and conversion applications have been discussed in detail in some very excellent review articles.…”
Section: Introductionmentioning
confidence: 99%